Professional uses of Facebook amongst university students in relation to searching for jobs: an exploration of activities and behaviours. (13th August 2020) - Alim, Sophia; AlShourbaji, Ibrahim
With Facebook use popular amongst students, more research is needed into the use of Facebook in a professional capacity amongst university students. This study investigates the professional uses of Facebook amongst university students, in relation to searching for jobs. The survey was distributed to university students around the world. A total of 101 responses were statistically collected and analysed. The obtained results show that networking with businesses was the most popular career related activity carried out on Facebook. A moderate positive association was also found between the amount of time spend on networking daily on Facebook and the number of job offers received as a result. Factors such as the size of Facebook network consulted during a job search and feelings towards Facebook had a weak association with the number of job offers received. Overall, this study has highlighted that Facebook can be used as a platform for professional uses.